The Effect of Supervision of Madrasah Principals and Ability to Use Technology on the Performance of MAN Teachers in Malang City - Akhmad Suhadak Solikin; Syamsul Bakri; Abdul Matin Bin Salman; Imdad Rabbani (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
Academic supervision is one of the important activities for schools or madrasas in order to create quality learning continuity. So that the teacher's problems have been solved, one of which is enjoying teachers in the use of information technology to realize planned and organized supervision activities. The purpose of this study was to determine the effect of principal supervision on teacher performance, the effect of using technology on teacher performance and the effect of principal supervision and use of technology on teacher performance. This quantitative research was conducted in Madrasah Aliyah Negeri 1 and 2 Malang City. The population is 244 people and the sample is 150 people. The results of this study prove that there is a significant positive effect of madrasa supervision on teacher performance as evidenced by the percentage of 6.1%. On the other hand, there is a significant positive effect between the use of technology on teacher performance, as evidenced by the percentage of 10.3%. There is also the influence of principal supervision and the use of technology on teacher performance by 16.5%. Thus, good teacher performance can be used a little through the implementation of supervision by the principal and finding teachers in information technology as well as several other factors mentioned in this study.